Facile preparation of conductive carbon-based membranes on dielectric substrates - Liu, Guoran; Xu, Guanchen (Frontiers in Chemistry, 2023)
Graphene has attracted much research attention due to its outstanding chemical and physical properties, such as its excellent electronic conductivity, making it as a useful carbon material for a variety of application fields of photoelectric functional devices. Herein, a new method for synthesizing conductive carbon membranes on dielectric substrates via a low-temperature thermodynamic driven process is developed. Although the obtained films exhibit low crystallinity, their electrical, wetting, and optical properties are acceptable in practice, which opens up a new avenue for the growth of carbon membranes and may facilitate the applications of transparent electrodes as potential plasma-free surface-enhanced Raman scattering (SERS) substrates.